ANALYSIS OF THE MORTALITY STRUCTURE IN HEMODIALYSIS PATIENTS - Shifris, I. M.; Dudar, I. O.; Gonchar, I. I.; Krot, V. F.; Krasyuk, E. K.; Aleksieva, N. G.; Khil, M. (Ukrainian Journal of Nephrology and Dialysis, 2017)
Studies of the mortality structure in patients receiving hemodialysis (HD) remain relevant and are the basis for developing measures and recommendations directed to increase the lifetime of patients. Aim. The aim was to study the assessment of death causes in patients who received programmed hemodialysis, based on the demographic and gender characteristics, the duration of dialysis treatment. Methods. Mortality causes in 137 patients who received programmed hemodialysis from 2007 to 2011 years in Kyiv City Scientific and Practical Center of Nephrology an Dialysis were analyzed. Results. The leading cause of death was cardiovascular complications, but their decreasing has been observed since 2008. Fatality rate in young and middle- aged women with cardiovascular diseases (CVD) was almost two times higher than that of men. At the same time CVD is a predominant cause of men’s death at the age older than 44. Cerebrovascular complications were permanently in the second place of the mortality structure. About 30% of deaths occurred during the first 90 days of HD treatment, 72,5% of them were among males. Conclusion. Gender characteristics influence the structure of death causes in patients received programmed hemodialysis depending on age.